Research of the Effect of Clearance on the Dynamic Characteristic of the Articulated Mechanism - Deng Yong; Liu Fuyun; Yang Mengjie; Wu Jianwei; Gan Lin (Jixie chuandong, 2015)
In order to study the effect of joint clearance on the dynamic characteristic of the articulated mechanism,an improved nonlinear contact collision model is established. By modifying the contact collision parameters,the contact state of collision is accurately described. Then the model is incorporated into ADAMS for dynamics simulation. The effects of loading frequency,loading acceleration and clearance size on the dynamic response of an articulated mechanism are studied. Through the contrasts of simulation and experimental results,the reliability of the model is verified. Thus,a certain reference for the research of the dynamic characteristic of the articulated mechanism with joint clearance is provided.